Impact of the fracture contact area on macro-dispersion in single rough fractures - Beaudoin, Anthony; Farhat, Mohamad (Comptes Rendus. Mécanique, 2021)
In the scientific literature, the study of the impact of the fracture contact area on macro-dispersion in single rough fractures is still an open question. In this work, we study numerically the combined effects of the fracture roughness and the fracture contact area on the non-Fickian transport in single rough fractures. In particular, we quantify the contribution of the fracture contact area on macro-dispersion. These objectives are achieved by estimating the macro-dispersion coefficient from Monte Carlo parallel numerical simulations in pure advection and advection–diffusion cases. When the fractional void $S_O$ is equal to 1 (i.e., for $σ _{lnb} < 0.25$), the Monte Carlo simulations show that macro-dispersion results of two contributions, dispersion caused by the heterogeneity of fracture apertures that induces a channelization of flow paths and molecular diffusion, as shown by the analytical solution proposed by Gelhar in 1993. When the fraction void $S_O$ is different from 1 (i.e., for $σ _{lnb} > 0.25$), a third mechanism plays in macro-dispersion. The presence of contacts or obstacles causes a disruption of flow paths. This mechanism is identical to that induced by the fracture roughness with a lower amplitude. Its amplitude is the function of the fractional void $S_O$.